Stomach Content Analysis of Mystacoleucus padangensis in Waters Naborsahan River and Toba Lake, Tobasa Regency, North Sumatra Province - Wahyu Budiharti; Chaidir P Pulungan; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Mystacoleucus padangensis is relatively small Cyprinids that commonly inhabit theToba Lake and surrounding waters. A study aims to understand the stomach contentand its relation with size, sex and level of maturity of gonads has been done onJanuary to April 2014. There were three stations, namely the Naborsahan River(Station I), river mouth of the Naborsahan River (Station II), and the Toba Lake(Stasiun III). There were 515 fishes captured, however only 52 fishes were used forstomach content analysis study as the other having almost empty stomach (stomachfullness index less than 50%. Parameters measured were Index of Preponderance(IP), type of food based on Total Length, sex, and maturity level. Results shown thatthe main food of this fish is Rotifera (IP 41.78%). Small fishes (less than 81 mm TL)tend consume Bacilliariophyceae (76.17%), medium sized (80 – 93 mm TL) fish tendto consume Cyanophyceae (39.87%), while the big fish (more than 139 mm TL)prefer to consume Rotifera 38.27-58.38%) and Xanthophyceae (52.51%). Based onsex, the male eat more Cyanophyceae (35.60%), while that of the female Rotifera(39.86%). Fish with relatively low maturity level (2nd and 3rd maturity levels) tend toeat Cyanophyceae (82.56%) and Bacilliariophyceae (76.29%) respectively, whilemature fish prefer Rotifers (81.58%). Based on data obtained, it can be concluded thatthe diet of M. padangensis was various, and it is related to body size, sex and gonadmaturity level.Keywords : Mystacoleucus padangensis, Stomach Content Analysis, PreponderanceIndex, Sumatera Utara